PERAN KELUARGA DALAM PENDIDIKAN SEKSUAL SEBAGAI PENCEGAHAN PENYIMPANGAN SEKSUAL ( LGBT ) PADA REMAJA DI KOTA BATAM - Rahayu Lestari (LP2M-Institut Agama Islam Abdullah Said Batam, 2023)
The full absence of the family will lead to abnormal behavior such as sexual deviation. The case of LGBT (Lesbian, Gay, Bisexual, Transgender) is currently on the rise as a result of the lack of family roles in all aspects, one of which is sexual education. The purpose of this study was to determine the extent to which the role of the family provides an understanding of sexual education so that adolescents do not commit sexual deviants (LGBT). This research is a qualitative research with a case study approach, namely the researcher conducts an in-depth exploration of all events, processes, activities that allow researchers to collect detailed data with various data collection procedures in a continuous time so that valid data is obtained. to something and explore the various experiences of parents in providing sexual education in a family. This research was conducted at the Embun Pelangi Foundation, Batam City. Data obtained from the field through observation, interviews, triangulation, and also documentation using purposive sampling technique. The results of this study are that (1) the role of the family is very important in efforts to prevent LGBT in adolescents. (2) Sexual education is very effective given in the family as an effort to prevent adolescents from being LGBT, such as recognizing one's own gender, providing an understanding of sex according to with age, bedroom separation, instilling shame, instilling the soul of masculinity, and femininity from an early age.